2021
DOI: 10.1002/pc.26051
|View full text |Cite
|
Sign up to set email alerts
|

Tribological and mechanical behaviors of mollusk shell‐ultrahigh molecular weight polyethylene bio‐composite

Abstract: This work is focused on the study of the tribological and mechanical properties of mollusk shell (MS)‐ultrahigh molecular weight polyethylene (UHMWPE) biocomposite against stainless steel. Wear tests were carried out on a reciprocating pin on disc apparatus. Tensile tests were achieved using a computerized universal traction machine, model EZ‐20 LLOYD. Rockwell hardness of the bio‐reinforced composite was carried out using an AFFRI universal hardness test. The coefficient of friction and wear rate were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Indeed, the stress-strain curve of all the MS-UHMWPE biocomposites can be divided into four major parts, namely; linear elastic deformation, plastic deformation, striction of the polymer, and its hardening. 25…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, the stress-strain curve of all the MS-UHMWPE biocomposites can be divided into four major parts, namely; linear elastic deformation, plastic deformation, striction of the polymer, and its hardening. 25…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly used to evaluate the friction and wear properties of material combinations employed in total joint replacements. [24][25][26] In this study, the sliding stroke was set to 30 mm per cycle. The sliding speed was equal to 30 mm/s, which corresponds to a frequency of 1 Hz.…”
Section: Wear Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the study also reported that kenaf fibers had increased the wear and friction coefficient of the composite. 127 Sidia and Bensalah 128 have studied mollusk shell (MS) and ultrahigh molecular weight polyethylene (UHMWPE) based biodegradable composites and measured the tribological properties of composites via coefficient of friction and wear tests. The study observed significantly reduced the coefficient of friction and wear rate, 0.10 and 7 × 10 À6 mm 3 /N-mm (30% improved) for MS (5 wt.…”
Section: Tribological Propertiesmentioning
confidence: 99%